Beam Manipulations With Compact Planar Dielectric Pancharatnam–Berry Phase Devices - Liu, Yachao; Wang, Guo Ping (Frontiers in Physics, 2022)
The growth spurt of novel planar optical devices in recent years has been greatly facilitated by the rapid development of artificial material designing and nanoprocessing technology. Traditional optical phase gradient devices cannot be scaled down to sub-wavelength size due to the confinement of the optical path difference required for versatile phase manipulation, so new strategies are urgently needed to design compact planar devices. Here, we develop a series of novel compact planar devices that break the thickness limitation by taking advantage of the superpositionable, polarization-dependent properties of the Pancharatnam–Berry phase. Among them, representative compact devices are fabricated using well-designed dielectric glass plates. Our compact devices therefore offer a novel and simple scheme to circumvent the accumulation of transmission loss in a cascade system of phase gradient devices.